Task-oriented programming of large redundant robot motion - Westkämper, Engelbert; Schraft, Rolf Dieter; Schweizer, Manfred; Fred Herkommer, T.; Meißner, Alexander (Robotics and computer-integrated manufacturing, 1998)
Large robots are a new domain of advanced robotics. Examples of their application fields are tasks like operations on large free-form surfaces, especially aircraft cleaning and removing paint from hulls. They are equipped with a programmable robot control comparable to a control system used for industrial robots. However, conventional teach-in methods are not able to manage the complexity of programming large redundant robot operation on free-form geometries. The Fraunhofer IPA has developed an innovative off-line programming system that allows the creation of robot motion programs which satisfy time and energy optimization criteria. This system helps to avoid collisions within the workspace and to fulfill conditions that arise from the robot kinematics and dynamics. This advanced programming system has been successfully used to generate motion programs for the world’s largest mobile robot, the aircraft cleaning manipulator SKYWASH. In this context offline programs for eleven different types of aircraft have been developed.